2014
DOI: 10.1371/journal.pone.0085355
|View full text |Cite
|
Sign up to set email alerts
|

Media Coverage of Medical Journals: Do the Best Articles Make the News?

Abstract: Background: News coverage of medical research is followed closely by many Americans and affects the practice of medicine and influence of scientific research. Prior work has examined the quality of media coverage, but no investigation has characterized the choice of stories covered in a controlled manner. We examined whether the media systematically covers stories of weaker study design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 24 publications
4
31
0
1
Order By: Relevance
“…We found a majority of online news articles reporting on peer-reviewed papers, however this may be partly explained by our exclusion of more general news articles that did not report on a specified study. Previous studies have highlighted inconsistent quality and accuracy of science news reporting practices at multiple levels, ranging from institutional press releases to news pieces [16,17,21], and found that study types with poorer methodology gain more media coverage than research based on stronger evidence [33][34][35]. Our analysis of reporting quality and study type distribution in online news is consistent with previous evidence of poor quality reporting by broadsheet news sources [19,20,23] and a bias towards primary research [6,9,46,47].…”
Section: Amberg -Figuresupporting
confidence: 88%
See 2 more Smart Citations
“…We found a majority of online news articles reporting on peer-reviewed papers, however this may be partly explained by our exclusion of more general news articles that did not report on a specified study. Previous studies have highlighted inconsistent quality and accuracy of science news reporting practices at multiple levels, ranging from institutional press releases to news pieces [16,17,21], and found that study types with poorer methodology gain more media coverage than research based on stronger evidence [33][34][35]. Our analysis of reporting quality and study type distribution in online news is consistent with previous evidence of poor quality reporting by broadsheet news sources [19,20,23] and a bias towards primary research [6,9,46,47].…”
Section: Amberg -Figuresupporting
confidence: 88%
“…However, there is limited literature on content bias in science news reporting. Quality and style have been shown to vary across news outlets [16,17], but even the largest newspapers with the best overall standards tend to cover more studies with poorer methodology and observational studies over RCTs or systematic reviews [33][34][35].…”
Section: Content Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Studier og forskningsresultater som publiseres i gode tidsskrifter, og med solid metode, får sjelden medieoppmerksomhet (8). Artikler som er av dårligere kvalitet, og med dårligere forskningsmetode, omtales oftere (9). Det kan skyldes at journalistene ikke har tid til å sette seg inn i sakene og lener seg for mye på tidsskriftenes pressemeldinger (10,11).…”
unclassified
“…A recent study reviewing media coverage of medical research found that newspapers were more likely to cover observational studies than randomised control trials and preferentially cover research with weaker methodology [10, 11]. However, in mitigation, journalists point to the fact that they have the often onerous task of making esoteric cancer science ‘interesting’ to the general public.…”
Section: Introductionmentioning
confidence: 99%